Designing the suburban church: the mid twentieth-century Roman Catholic churches of Reynolds & Scott. (April 2017) - Proctor, Robert
Abstract: The pioneering modern movement, liturgically centred, church architecture of the mid twentieth century has become increasingly well documented and understood. Yet, for a long time before the Second Vatican Council most architects and clergy rejected this movement, maintaining traditional approaches and architectural forms. The basilican type dominated Roman Catholic church architecture in mid twentieth-century Britain, drawing loosely on Gothic or Byzantine and Romanesque models, and widely built in the new suburbs of expanding cities. As a typical landmark feature of such suburbs, the conventional church demands to be taken seriously and understood. This article draws on recent work on suburban and middle-class culture to interpret a body of such churches by a prolific firm of church architects, Reynolds & Scott of Manchester. It makes use of a hitherto unexplored archive of the practice's drawings, an interview with a surviving partner, parish and diocesan archives, and consideration of many of the buildings. The conventional basilican church can be reassessed through this evidence. It presents a type of creativity and a design approach that differ from the values embraced by modernism, but that nevertheless engage with the modernity of the suburb in a complex hybridity between the modern and traditional, the sacred and the secular, religious and domestic cultures, the particular, the transnational and the universal. Highlights: Presents a detailed study of a prolific 'traditional' twentieth-century church architecture practice. Uses newly-discovered material, particularly drawings, and an architect interview. Proposes new interpretations of mid twentieth-century churches using cultural theories of the suburb. Develops an original analysis of design processes using theories of the vernacular and the middlebrow.